2011
DOI: 10.1016/j.anorl.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and physiology of cerebrospinal fluid

Abstract: The cerebrospinal fluid (CSF) is contained in the brain ventricles and the cranial and spinal subarachnoid spaces. The mean CSF volume is 150 ml, with 25 ml in the ventricles and 125 ml in subarachnoid spaces. CSF is predominantly, but not exclusively, secreted by the choroid plexuses. Brain interstitial fluid, ependyma and capillaries may also play a poorly defined role in CSF secretion. CSF circulation from sites of secretion to sites of absorption largely depends on the arterial pulse wave. Additional facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
432
1
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(514 citation statements)
references
References 38 publications
13
432
1
20
Order By: Relevance
“…Animal studies have shown a direct communication between the adventitia of cerebral arteries and surrounding CSF. 32 If such a communication exists in humans, it could facilitate fungal angioinvasion in the major CNS arteries. The organism's metabolic requirements for oxygen and iron concentrated in arterial erythrocytes may be an impetus, and protease digestion or physical disruption of the vessel wall may provide the means, for angioinvasion, as described for other fungi.…”
Section: Pathology Of Exserohilum Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown a direct communication between the adventitia of cerebral arteries and surrounding CSF. 32 If such a communication exists in humans, it could facilitate fungal angioinvasion in the major CNS arteries. The organism's metabolic requirements for oxygen and iron concentrated in arterial erythrocytes may be an impetus, and protease digestion or physical disruption of the vessel wall may provide the means, for angioinvasion, as described for other fungi.…”
Section: Pathology Of Exserohilum Infectionsmentioning
confidence: 99%
“…Although the dura is typically regarded as impervious and contiguous with the epineurium of spinal nerves, there is evidence that normal CSF resorption involves some flow across the dura and cranial and spinal nerve sheaths, with uptake by lymphatics. 32,39,40 This implies some degree of dural permeability, which may be another potential means of initial fungal entry into the CSF.…”
Section: Pathology Of Exserohilum Infectionsmentioning
confidence: 99%
“…There are also the unpaired third and fourth ventricles. The CSF volume is about 150 ml, and approximately 450 ml are produced each day, which means that the CSF is replaced three times a day [5]. In the classic CSF circulation model, known as the "bulk flow model" [6], the CSF is produced by the choroid plexus which is located primarily in the lateral ventricles and to a lesser extent also in the third ventricle and on the roof of the fourth ventricle.…”
Section: Anatomy and Physiological Basismentioning
confidence: 99%
“…Así también, la presencia de comorbilidades en este grupo de estudio no demostró significancia estadística (p 0,5). (12,19,(21)(22)(23)(24) Los hallazgos microbiológicos de este estudio coinciden con el de la literatura . Se encontró un porcentaje similar entre cocos Gram positivos y bacilos Gram negativos, siendo S. aureus, S. epidermidis, A. baumanii, y K. pneumoniae los gérmenes más frecuentemente aislados.…”
Section: %unclassified